Volume 3A: Heat Transfer 2013
DOI: 10.1115/gt2013-95412
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Flow and Heat Transfer in a Lattice (Matrix) Cooling Channel

Abstract: Flow and heat transfer of lattice cooling channel are investigated numerically. Firstly, simulations are performed for two channels to reproduce the experimental results reported in open literatures. Based on the literatures, sub-channels consisting lattice network are designed with aspect ratio of near unity and crossing angle of 45 degrees. Predicted heat transfer patterns of primary surfaces have agreed qualitatively and quantitatively well with the experimental results. Cooling air turns mainly through tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To understand the flow and heat transfer mechanism, flow visualization of the lattice cooling duct is needed; however, the complicated geometry makes it quite hard due to difficulty with optical access. Therefore, numerical investigations have been performed to discuss the flow characteristics [7][8][9][10][11]. Most predicted results have shown similar trends to those described by Khalatov and Nam [2]; however, prediction accuracy of the velocity field has never been quantitatively evaluated.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation
“…To understand the flow and heat transfer mechanism, flow visualization of the lattice cooling duct is needed; however, the complicated geometry makes it quite hard due to difficulty with optical access. Therefore, numerical investigations have been performed to discuss the flow characteristics [7][8][9][10][11]. Most predicted results have shown similar trends to those described by Khalatov and Nam [2]; however, prediction accuracy of the velocity field has never been quantitatively evaluated.…”
Section: Figmentioning
confidence: 98%
“…In Refs. [6] and [10], it is suggested that heat transfer from the side walls significantly contributes to the overall heat release. By comparing measured heat transfer coefficient distributions among three surfaces, the amount of contribution will be discussed.…”
Section: Figmentioning
confidence: 99%
“…Their research also shows that the matrix cooling channels with two inlet subchannels have higher heat transfer and lower pressure loss than those with four inlet subchannels. Hagari and Ishida 5 conducted numerical investigations on matrix cooling channels to examine the impact of rib inclination angle on the flow and heat transfer. The results show that a 27% increase of rib inclination angle leads to 30% increase in total heat flux by enhancing the translation between the subchannels and impingement at turning regions.…”
Section: Introductionmentioning
confidence: 99%